"You Don't Have Time to Think Up There. If You Think You're Dead" – A Corpus-assisted Study of Discursive Strategies to Engage Readers in Corporate Blogs - Goźdź-Roszkowski, Stanisław; Fronczak, Katarzyna (Research in Language, 2020)
This study investigates recurrent language resources employed in corporate blogs to connect with readers and (to a lesser extent) express authorial positions. It is based on the premise that constructing identity and enhancing image underpins most, if not all, corporate discourse and blogs are no exception. Based on a corpus of 500 different posts (totalling 318,296 words) from the Business Process Outsourcing and Information Technology sectors, we use standard Corpus Linguistics (Partington et al. 2013) techniques (keywords, cluster analysis, concordancing) to identify linguistic features associated with the expression of engagement: reader pronouns and their co-occurrence with selected modal verbs, questions, adverbs marking shared knowledge and directives. These are then interpreted in in terms of a model of textual interactions proposed in Hyland (2005). We argue that the communication found in this relatively new and underresearched genre is essentially effected one-way establishing a pseudo-dialogue, with virtually no or very low level of interactivity between blog writers and blog readers.